An Analysis of Japanese EFL Learners’ Lexical Network Changes - Aotani, Noriko; Takahashi, Shin’ya (Frontiers in Education, 2021)
In order to compare Japanese EFL learners’ lexical knowledge before and after undertaking extensive reading tasks, this study picked up eight words from the reading material and investigated how learners’ perceived relationship between these words changed during the task. Data were collected from 58 Japanese EFL learners who were divided into three groups, each of which was given the same reading material but with different tasks (translation task, multiple-choice question task, and no task (control)). Participants judged the degree of relationship between target words twice, before and after the assigned task. The results revealed that participants in the translation task group tended to find the relationships between the words more easily than the participants in other groups, and they were also more aware of changes in their own ability to recognize word association. In addition, the authors also analyzed the data by using AMISESCAL (Asymmetric von Mises Scaling), a statistical model that visualizes asymmetric relations among elements on a two-dimensional map. Visualization of learners’ lexical network threw some light on the restructuring process of how words were interconnected in their lexical representation.